Daratumumab-induced acute angle closure glaucoma: bone marrow transplantation as a possible risk factor and atropinization as a potential solution - Cansu Yuksel Elgin; Ahmet Fırat Atseven; Ofeliya Mammadzada; Özcan Ocakoğlu (BMC Ophthalmology)
Abstract This case report describes a 29-year-old female with recurrent T-cell Acute Lymphoblastic Leukemia who developed acute angle closure glaucoma (AACG) following daratumumab infusion. The patient, with a history of bone marrow transplantation and head-neck radiotherapy, experienced sudden eye pain and blurred vision minutes after treatment initiation. Ophthalmological examination revealed bilateral closed angles and elevated intraocular pressure. Ultrasound biomicroscopy showed ciliary malrotation and effusion, suggesting choroidal effusion secondary to daratumumab. The condition was successfully managed with topical medications and subsequent infusions were administered with atropine premedication, preventing recurrence. This case highlights bone marrow transplantation as a potential risk factor for daratumumab-induced AACG and demonstrates the effectiveness of atropinization in managing this complication.